PENDAMPINGAN PEMANFAATAN RUMPUT GAJAH SEBAGAI PAKAN HEWAN TERNAK DI DESA SENTULAN KECAMATAN BANYUANYAR KABUPATEN PROBOLINGGO - Naila Sakinah (Kalam Nusantara Institute, 2023)
Diversity in providing forage as ruminant livestock feed is important to do. With the diversification of types of forage, the nutritional needs of ruminants are expected to be fulfilled. One variant that is being developed and introduced to breeders as forage for livestock is elephant grass. Sentulan is a village in Banyuanyar sub-district, Probolinggo district which has a population of 2,538 people and an area of ​​295,695 km². Elephant grass in the Sentulan area only exists in a few areas, because many residents do not know the benefits of elephant grass and its contents. So it is necessary to provide material about the benefits of elephant grass. This activity was carried out using the ABCD (Asset Based Community Development) approach with the Appreciative Inquiry method in several stages. The purpose of this activity is to utilize elephant grass in Sentulan Village to make the existing ecosystem easier. The methods used in this activity are Discovery, Dream, Design, and Destiny. The result of this activity is that the service program activities are carried out well by following several stages in its implementation. In conclusion, this activity can improve the quality of human resources for the Sentulan village community to utilize elephant grass as ruminant animal feed so that it is hoped that it will not be difficult to find animal feed and save the existing ecosystem.